Expression of Id-1 and VEGF in non-small cell lung cancer - Kim, Mee-Seon (e-Century Publishing Corporation, 2013)
Angiogenesis is essential for invasive tumor growth and metastasis. Bevacizumab has been widely used for the treatment of non-small cell lung cancer (NSCLC). Various studies clearly demonstrate the relevance of Id-1 and VEGF in angiogenesis. The aim of this study was to establish the role of Id-1 expression in tumor progression and angiogenesis in relation to VEGF in NSCLC. Seventy five patients underwent surgery for lung cancers. The expressions of Id-1 and VEGF in NSCLC samples were determined by immunohistochemistry. Expression of Id-1 and VEGF showed a close correlation in NSCLC (p < 0.001). In addition, Id-1 strong expression group showed high incidence of metastasis in multivariate analysis (p = 0.028). Id-1 strong expression group had short metastasis-free survival (p = 0.008) and short recurrence-free survival (p = 0.027). Strong Id-1 expression in NSCLC had a poor prognosis in association with VEGF expression. Id-1 may function in tumor growth and progression via angiogenesis. Therefore, Id-1 is considered to be a candidate for new therapeutic target and a prognostic factor in NSCLC.